Cost-effectiveness of l-glutamine versus crizanlizumab for adults with sickle cell disease: model focused on reducing pain episode costs from Qatar’s healthcare perspective - Ahmad M Adel (21767351) (2024)
Objectives Treatment options for preventing vaso-occlusive crises among sickle cell disease patients are on the rise, especially if hydroxyurea treatment has failed. This economic analysis is conducted to assess the comparative clinical effectiveness, safety, and acquisition cost of l-glutamine and crizanlizumab for older adolescents and adults (⩾16 years old) with sickle cell disease in Qatar, with an emphasis on treatment costs and acute pain crises. Methods We conduct a decision-tree model, where we compare the clinical and economic outcomes of two novel Food and drug administration (FDA)-approved medications which are available in Qatar; l-glutamine and crizanlizumab over a time horizon of 1 year in a hypothetical cohort of adult sickle cell disease patients from a Qatar healthcare perspective. The main outcome is incremental cost per sickle cell disease-related acute pain crises averted. Model clinical parameters were derived from individual drug randomized trials, published literature, whereas cost parameters from Qatar healthcare payer system (2020–2021). A sensitivity analysis was carried out, and the study results were robust around model inputs. Costs were converted to 2020 US dollars. Results Study results showed that both treatment modalities’ costs were the main driver of this analysis, with an average annual cost of the treatments per patient being $189,014 for crizanlizumab (5 mg/kg), $143,798 for crizanlizumab (2.5 mg/kg), and $74,323 for l-glutamine. The probability of no first-time sickle cell disease-related vaso-occlusive crises averted was 0.001/year for glutamine, 0.26/year for crizanlizumab (5 mg/kg), and 0.34/year for crizanlizumab (2.5 mg/kg). Lower dose crizanlizumab (2.5 mg/kg) dominated the higher one (5 mg/kg). The incremental cost-effectiveness ratio of crizanlizumab (2.5 mg/kg), when compared to l-glutamine was $81,265 per sickle cell disease-related vaso-occlusive crises averted. When comparing crizanlizumab (5 mg/kg) and l-glutamine, crizanlizumab (5 mg/kg) showed higher efficacy, yet the crizanlizumab incremental cost-effectiveness ratio was at $459,620 than l-glutamine. Conclusions Crizanlizumab (2.5 mg/kg) may be a cost-effective intervention, yet it is not the approved dose for preventing vaso-occlusive crises in adolescents and adults with sickle cell disease. Crizanlizumab (5 mg/kg) was more cost-effective than the approved l-glutamine per sickle cell disease vaso-occlusive crisis prevented. Of note, we primarily focused on modeling acute vaso-occlusive pain, which limited our ability to consider other key outcomes in sickle cell disease. Other Information Published in: SAGE Open Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/20503121231224551